A low surface energy, corrosion-resistant, high entropy composite coating for die casting mold and preparation method thereof

By applying a high-entropy composite coating composed of multi-layer structure on the mold, the problem of resistance to aluminum corrosion in high-temperature environments is solved, and the mold is high wear resistance, corrosion resistance and low surface energy are achieved, which extends the service life of the mold and improves the processing performance.

CN116121714BActive Publication Date: 2025-04-15IKD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310144407.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-04-15
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

When the prior art improves the service life of the mold, the problem of high-entropy coating resistance to aluminum liquid corrosion has not been fully solved, resulting in the mold being easily corroded in high-temperature environments.

Method used

The coating is prepared by arc ion plating technology using a gradient structure composed of a bonding layer, a transition layer, a hardening layer, a wear-resistant layer, a liquid aluminum corrosion resistance layer and a low-surface energy aluminum liquid layer.

Benefits of technology

It achieves good wear resistance, corrosion resistance and low surface energy of the mold in high temperature environments, extends the service life of the mold, and improves processing performance and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116121714B_ABST
    Figure CN116121714B_ABST
Patent Text Reader

Abstract

The invention discloses a low surface energy corrosion resistant high entropy composite coating for a die casting mold and a preparation method thereof. The coating comprises a gradient structure consisting of a bonding layer, a transition layer, a hardening layer, a wear resistant layer, an aluminum liquid corrosion resistant layer and a low surface energy aluminum liquid hydrophobic layer; the bonding layer is a pure CrTi layer; the transition layer is a CrTiN transition metal ceramic layer; the hardening layer is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear resistant layer is a TiVZrNbHfCrBN high entropy alloy nitride layer; the aluminum liquid corrosion resistant layer is a TiVZrNbHfCrBON layer; the low surface energy aluminum liquid hydrophobic layer is a TiVZrNbHfCrBO oxide layer; the TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings are combined to construct a gradient high entropy composite coating, and the advantages of the three properties are utilized to construct a coating with excellent comprehensive properties of wear resistance, corrosion resistance and low surface energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thin film materials, and in particular to a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold applied to surface treatment of a die-casting mold and a preparation method thereof. Background Art

[0002] With the development of the domestic economy and the improvement of people's living standards, domestic automobile sales have risen sharply, which has greatly promoted the development of the domestic die-casting industry, especially the aluminum alloy die-casting industry. With the increasing calls for lightweight domestic automobiles, the optimization and upgrading of the automotive industry has also been gradually implemented, and gray iron castings have been gradually replaced by aluminum castings, which has stimulated the rising demand for aluminum alloy die-castings. In addition, with the rapid development of the global die-casting industry, the demand for aluminum alloy die-castings in all walks of life is also increasing, and the development prospects of the die-casting industry are very broad. The integrated die-casting technology was first proposed by Tesla in 2019, and this technology was applied to the production of the rear floor of the Model Y in 2020, which has a significant weight reduction effect. After the integrated die-casting technology is used, the original 80 stamping and welding parts of the rear floor are integrated into one component, which enables the rear floor to achieve a 10% weight reduction. What is more noteworthy is that the cost has also dropped by 40%.

[0003] For the integrated die-casting process, the die-casting machine is the key equipment. At the same time, from the perspective of downstream demand for die-casting machines, automobiles are also the largest source, accounting for more than 70%. The previous demand for die-casting machines was more for small tonnage, below 4,500 tons. With the application of the integrated battery body design led by Tesla, the demand for large die-casting machines has increased significantly. The tonnage of the die-casting machine corresponding to the front and rear floor and battery base is between 6000T and 12000T, and the integrated lower body also needs to use a die-casting machine of more than 10,000T for production. Compared with the previous die-casting machine, the weight has increased significantly, and the integrated die-casting technology has spawned the demand for large die-casting machines. In other words, if you want to build an integrated die-casting production line workshop in the future, you must purchase a large die-casting machine. At present, the application of integrated die-casting technology is in its infancy, and its popularity in automobiles is still relatively low. However, with the development of electric vehicles, it is only a matter of time before the optimization of production processes and the widespread application of integrated die-casting technology are used. It is estimated that the penetration rate of one-piece die-casting will reach 84% by 2030, and the global market size will be approximately 60 billion yuan. One-piece die-casting technology will enable the global die-casting machine market to show a sustained high growth trend in the next decade.

[0004] Integrated die casting places higher demands on molds. High entropy coatings have more outstanding advantages than conventional ternary and quaternary nitride coatings in terms of high-temperature oxidation resistance and wear resistance due to the high entropy effect in thermodynamics and the slow diffusion effect in crystallography. Compared with conventional nitride coatings, high entropy coatings have better structural stability and surface oxidation resistance in high-temperature resistant occasions. Due to the characteristics of multiple principal elements, the oxide film has complex composition and dense structure, can withstand intense temperature loads, has good protection for the base material, and can meet the special needs of temperature resistance and oxidation resistance under harsh working conditions.

[0005] The invention patent text entitled "High-temperature-resistant nano-multilayer self-lubricating coating and preparation method for die-casting core pulling" with application publication number CN112501571A discloses that the coating includes a bonding layer, a transition layer, a gradient layer and a high-temperature-resistant self-lubricating layer which are sequentially attached to the outside of the die-casting core pulling, the bonding layer is a pure SiB layer, the transition layer is a SiBN layer, the gradient layer is a SiTiC-DLC coating, and the high-temperature-resistant self-lubricating layer is a SiTiC-DLC / BTiC-DLC nano-multilayer film composed of SiTiC-DLC and BTiC-DLC.

[0006] The invention patent text entitled HfZrWMoVNbN / CrSiN high entropy alloy nanocomposite coating die-casting aluminum mold and its preparation method with application publication number CN111014616A discloses that the coating includes a bonding layer, a transition layer, a supporting layer, and an impact-resistant and heat-resistant layer; the bonding layer is a pure Nb layer prepared by high-energy bombardment of an arc ion plating method, the transition layer is a NbN transition metal ceramic layer, the supporting layer is a NbN / HfZrWMoVNbN high entropy alloy nitride nano-multilayer film, and the impact-resistant and heat-resistant layer is a HfZrWMoVNbN / CrSiN nano-multilayer film.

[0007] In order to improve the service life of the mold, the above patent focuses on the temperature resistance and wear resistance of the coating. However, there are currently deficiencies in the research on the resistance of high entropy coatings to molten aluminum corrosion, and it is urgent to develop new high entropy composite coating materials that are resistant to molten aluminum corrosion. Summary of the invention

[0008] The invention provides a low surface energy corrosion-resistant high entropy composite coating for a die-casting mold and a preparation method thereof.

[0009] The technical solution adopted by the present invention to solve the above technical problems is: a low surface energy corrosion-resistant high entropy composite coating for a die-casting mold, comprising a gradient structure composed of a bonding layer, a transition layer, a hardening layer, a wear-resistant layer, an aluminum liquid corrosion-resistant layer, and a low surface energy aluminum liquid repellent layer; the bonding layer is a pure CrTi layer; the transition layer is a CrTiN transition metal ceramic layer; the hardening layer is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer is a TiVZrNbHf CrBN high entropy alloy nitride layer; the aluminum liquid corrosion-resistant layer is a TiVZrNbHfCrBON layer; the low surface energy aluminum liquid repellent layer is a TiVZrNbHfCrBO oxide layer.

[0010] The preferred technical solution adopted by the present invention to solve the above technical problems is: the CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers, the CrTiN single layer thickness is 8 to 20 nanometers, the TiVZrNbHfCrBN single layer thickness is 4 to 20 nanometers, and the coating modulation period is 12 to 40 nanometers.

[0011] The preferred technical solution adopted by the present invention to solve the above technical problem is: the TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals of the columnar crystal structure is 30 to 100 nanometers.

[0012] The preferred technical solution adopted by the present invention to solve the above technical problems is: the TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline scale is 30 to 50 nanometers and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer.

[0013] The preferred technical solution adopted by the present invention to solve the above technical problem is: the crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0014] The preferred technical solution adopted by the present invention to solve the above technical problems is: the thickness of the bonding layer is 5 to 30 nanometers, the thickness of the transition layer is 200 to 1000 nanometers, the thickness of the hardening layer is 1200 to 4000 nanometers, the thickness of the wear-resistant layer is 2000 to 3000 nanometers, the thickness of the anti-aluminum liquid corrosion layer is 500 to 1000 nanometers, and the thickness of the low surface energy aluminum-phobic liquid layer is 500 to 1000 nanometers.

[0015] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a low surface energy corrosion-resistant high entropy composite coating for a die-casting mold, wherein the coating is prepared by arc ion plating, which at least comprises the following steps:

[0016] Step 1: In an argon environment, the die-casting mold is cleaned by plasma etching;

[0017] Step 2: The CrTi target located on the first side of the die-casting mold is turned on, and the die-casting mold is rotated to evaporate the CrTi at high temperature and move it to the surface of the die-casting mold at high speed under the action of high bias voltage, and the CrTi ions are metallurgically combined with the die-casting mold matrix, and a pure CrTi layer is deposited as a bonding layer;

[0018] Step 3: Based on step 2, nitrogen is introduced, and the nitrogen reacts with CrTi to form a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer;

[0019] Step 4: On the basis of step 3, the TiVZrNbHfCrB target located on the second side of the die-casting mold away from the CrTi target is opened, and a CrTiN single layer is deposited when the die-casting mold is rotated toward the CrTi target, and a TiVZrNbHfCrBN single layer is deposited when the die-casting mold is rotated toward the TiVZrNbHfCrB target, and this process is repeated to alternately form a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film as a hardening layer on the surface of the CrTiN transition metal ceramic layer;

[0020] Step 5: The CrTi target is closed, and the die-casting mold is rotated to form a TiVZrNbHfCrBN high entropy alloy nitride layer outside the hardening layer as a wear-resistant layer;

[0021] Step 6: Based on step 5, oxygen is then introduced, and in a nitrogen and oxygen atmosphere, the opened TiVZrNbHfCrB target is evaporated at high temperature to deposit a TiVZrNbHfCrBON layer outside the wear-resistant layer as an anti-aluminum liquid corrosion layer;

[0022] Step 7: Based on step 6, the nitrogen is turned off, and in an oxygen atmosphere, the opened TiVZrNbHfCrB target is evaporated at high temperature and deposited outside the aluminum liquid corrosion resistance layer to form a TiVZrNbHfCrBO oxide layer as a low surface energy aluminum liquid repellent layer.

[0023] The preferred technical solution adopted by the present invention to solve the above technical problem is: step 1 is carried out at 250-550°C.

[0024] The preferred technical solution adopted by the present invention to solve the above technical problems is: step 2 is carried out under the conditions of 0.1~0.5Pa, -50V~-100V, step 3 is carried out under the conditions of 0.1-2Pa, -100V~-250V; step 4 is carried out under the conditions of 0.5~2.3Pa, -50~-250V; step 5 is carried out under the conditions of 2~4Pa, -50~-250V; step 6 is carried out under the conditions of 2~4Pa, -50~-200V; step 7 is carried out under the conditions of 2~4.3Pa, -50~-200V.

[0025] The preferred technical solution adopted by the present invention to solve the above technical problem is: natural cooling after step seven.

[0026] Compared with the prior art, the advantages of the present invention are that a gradient film layer is constructed by using multiple materials including TiVZrNbHfCrBON, TiVZrNbHfCrBN and TiVZrNbHfCrBO, and the performance advantages of the three materials are utilized to construct a coating with excellent comprehensive performances of wear resistance, corrosion resistance and low surface energy; the change of the coating composition is mainly achieved by introducing gas, and multiple complex target materials are not used, thereby reducing the use cost of the target material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and preferred embodiments, but those skilled in the art will appreciate that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be used as a limitation on the scope of the present invention. In addition, unless otherwise specified, the drawings are only schematically representing the composition or structure of the described objects and may contain exaggerated displays, and the drawings are not necessarily drawn to scale.

[0028] Figure 1 A schematic diagram of an apparatus for preparing a low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to the present invention;

[0029] Figure 2 This is a schematic diagram of the composite structure of the low surface energy, corrosion-resistant, high entropy composite coating of the die-casting mold provided by the present invention. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It will be appreciated by those skilled in the art that these descriptions are only illustrative and exemplary and should not be construed as limiting the scope of protection of the present invention.

[0031] Figure 1The device used in the first to fifth embodiments is shown. The vacuum chamber of the device is surrounded by the furnace wall, and the size of the vacuum chamber is 1000x1000x1000mm. The vacuum chamber is provided with a vacuum port 40, and the vacuum pumping unit evacuates the vacuum chamber through the vacuum port 40. The four corners of the vacuum chamber are heaters 20, and the heating power is 10 to 30 kilowatts to improve the heating efficiency. The arc targets are installed on the furnace wall in a row, and the CrTi target 60 and the TiVZrNbHfCrB target 30 are installed respectively, and the sample is mounted on a rotatable workpiece rack 50. The etching source 10 is installed on the door. This layout greatly increases the plasma density in the vacuum chamber, and the workpiece is completely immersed in the plasma. The deposition rate, hardness and adhesion of the coating are greatly improved. Due to the optimization of the target structure, the magnetic field distribution is more uniform, so that the arc burns evenly on the target surface, and the uniformity of the coating is improved.

[0032] The arc ion plating technology used in embodiments 1 to 5 is similar to the current coating equipment. At the same time, the coating equipment has a simple structure, is easy to control, and has good industrial application prospects.

[0033] The following further describes Examples 1 to 6. Examples 1 to 6 use different process parameters to prepare a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold.

[0034] Embodiment 1

[0035] The steps of preparing a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold include:

[0036] Step 1: Open Figure 1 In the equipment shown, the heater 20 is turned on, the temperature of the vacuum chamber is adjusted to 250°C, argon gas is introduced, the etching source 10 is turned on, and the die-casting mold is subjected to arc discharge plasma etching. After the ion cleaning is completed, the surface of the mold substrate is in a relatively clean state. Ion etching cleaning is a prerequisite for adhesion. However, the subsequent preparation process is also a necessary supplement to obtain high adhesion. Generally, the ion bombardment method is used to further improve the adhesion.

[0037] Step 2: After the plasma etching is completed, the CrTi target 60 located on the first side of the die-casting mold is opened. Under the conditions of 0.1Pa and -50V, the die-casting mold is rotated, and the CrTi on the CrTi target 60 is evaporated at high temperature by an arc ion plating method and moved to the surface of the die-casting mold at high speed under the action of high bias voltage. A negative high voltage of 800V is applied to the surface of the die-casting mold. The high voltage has an accelerating effect on the ionized die-casting mold ions. The accelerated die-casting mold ions will collide with the die-casting mold surface at high speed. The collision process will generate high temperature, and the CrTi ions will form a metallurgical bond with the die-casting mold substrate, thereby depositing a 5-nanometer thick pure CrTi layer as a bonding layer.

[0038] Step 3: Based on step 2, change the pressure and voltage, and introduce nitrogen at 0.1Pa, -100V. Nitrogen reacts with CrTi to generate a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer. The thickness of the deposited CrTiN transition metal ceramic layer is 200 nanometers.

[0039] Step 4: Based on step 3, the pressure and voltage are changed, and the TiVZrNbHfCrB target 30 located on the second side of the die-casting mold away from the CrTi target is turned on under the conditions of 0.5Pa and -50V. When the workpiece holder 50 carries the die-casting mold and rotates toward the CrTi target, a CrTiN single layer is deposited, and the thickness of the CrTiN single layer is 8 nanometers; when the workpiece holder 50 carries the die-casting mold and rotates toward the TiVZrNbHfCrB target 30, a TiVZrNbHfCrBN single layer is deposited, and the thickness of the TiVZrNbHfCrBN single layer is 4 nanometers. This is repeated, and the modulation period is 12 nanometers, so that a 1200 nanometer thick CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is alternately formed on the surface of the CrTiN transition metal ceramic layer as a hardening layer.

[0040] Step 5: close the CrTi target, and when the workpiece holder 50 carries the die-casting mold to rotate under the condition of 2Pa and -50V, further arc ion plate the TiVZrNbHfCrB target 30 to form a 2000 nm thick TiVZrNbHfCrBN high entropy alloy nitride layer as a wear-resistant layer outside the hardening layer;

[0041] Step 6: Based on step 5, without changing the pressure and voltage, oxygen is introduced, and in the nitrogen and oxygen atmosphere, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature, and a 500 nanometer thick TiVZrNbHfCrBON layer is deposited outside the wear-resistant layer as an anti-aluminum liquid corrosion layer.

[0042] Step 7: On the basis of step 6, continue to maintain the pressure and voltage, turn off the nitrogen, and in an oxygen atmosphere, open the TiVZrNbHfCrB target 30 for high temperature evaporation, and deposit a 500 nanometer thick TiVZrNbHfCrBO oxide layer outside the aluminum liquid corrosion resistance layer as a low surface energy aluminum liquid repellent layer.

[0043] Step 8: After the preparation is completed, the die-casting mold is naturally cooled to obtain a low surface energy, corrosion-resistant, high-entropy composite coating on the surface of the die-casting mold with good bonding strength, wear resistance, temperature resistance, and resistance to aluminum liquid corrosion to cope with the effect of high-temperature aluminum liquid.

[0044] like Figure 2As shown, the low surface energy corrosion-resistant high entropy composite coating of the above-mentioned die-casting mold includes a gradient structure composed of a bonding layer 2, a transition layer 3, a hardening layer 4, a wear-resistant layer 5, an anti-aluminum liquid corrosion layer 6, and a low surface energy aluminum-phobic liquid layer 7 from the surface of the die-casting mold 1 from the inside to the outside; the bonding layer 2 is a pure CrTi layer; the transition layer 3 is a CrTiN transition metal ceramic layer; the hardening layer 4 is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer 5 is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-aluminum liquid corrosion layer 6 is a TiVZrNbHfCrBON layer; the low surface energy aluminum-phobic liquid layer 7 is a TiVZrNbHfCrBO oxide layer.

[0045] The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers. The number of layers of the hardening layer 4 in the figure is only an example to indicate that it is a multi-layer alternating superposition structure, and does not reflect the actual number.

[0046] The TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals in the columnar crystal structure is 30-100 nanometers.

[0047] The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline size is 30 to 50 nanometers, and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer. The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0048] The general high entropy coating is mainly composed of nitrides, which mainly improve the wear resistance life of the mold. However, the coating of this embodiment requires not only high wear resistance, but also good resistance to aluminum liquid corrosion.

[0049] Compared with conventional die-casting mold coatings, this embodiment makes full use of nano multi-layer composite and gradient composite coating technology to form a gradual change in structure and composition. The coating and the substrate are metallurgically bonded to improve the compatibility of the coating and the substrate, and have good adhesion. Compared with conventional arc ion plating technology, the multi-layer structure technology is used to inhibit the growth of columnar crystals and improve the density of the coating, which not only improves the corrosion resistance of the coating, but also greatly improves the wear resistance. Fourth, the present invention combines TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings to construct a gradient high entropy composite coating, and uses the advantages of the performance of the three to construct a coating with excellent comprehensive performance of wear resistance, corrosion resistance and low surface energy.

[0050] The TiVZrNbHfCrBON high entropy composite coating die-casting mold prepared by the present invention has good bonding force and wear resistance, temperature resistance and aluminum liquid corrosion resistance, ensures the long-term stable operation of the die-casting mold, greatly improves the processing performance of the die-casting mold, stabilizes the processing quality, improves the processing efficiency, and reduces the production cost of the manufacturer.

[0051] In this embodiment, the change of coating composition is mainly achieved by introducing gas, without using a variety of complex target materials, which reduces the cost of target materials, makes the preparation of coating more economical, and makes the process more convenient.

[0052] Embodiment 2

[0053] The steps of preparing a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold include:

[0054] Step 1: Open Figure 1 In the equipment shown, the heater 20 is turned on, the temperature of the vacuum chamber is adjusted to 550°C, argon gas is introduced, the etching source 10 is turned on, and the die-casting mold is subjected to arc discharge plasma etching. After the ion cleaning is completed, the surface of the mold substrate is in a relatively clean state. Ion etching cleaning is a prerequisite for adhesion. However, the subsequent preparation process is also a necessary supplement to obtain high adhesion. Generally, the ion bombardment method is used to further improve the adhesion.

[0055] Step 2: After the plasma etching is completed, the CrTi target 60 located on the first side of the die-casting mold is turned on. Under the conditions of 0.5Pa and -100V, the die-casting mold is rotated, and the CrTi on the CrTi target 60 is evaporated at high temperature by an arc ion plating method and moved to the surface of the die-casting mold at high speed under the action of high bias voltage. A negative high voltage of 1000V is applied to the surface of the die-casting mold. The high voltage has an accelerating effect on the ionized die-casting mold ions. The accelerated die-casting mold ions will collide with the surface of the die-casting mold at high speed. The collision process will generate high temperature, and the CrTi ions will form a metallurgical bond with the die-casting mold substrate, thereby depositing a 30-nanometer-thick pure CrTi layer as a bonding layer.

[0056] Step 3: Based on step 2, change the pressure and voltage. Under the conditions of 2Pa and -250V, introduce nitrogen. Nitrogen reacts with CrTi to generate a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer. The thickness of the deposited CrTiN transition metal ceramic layer is 1000 nanometers.

[0057] Step 4: Based on step 3, the pressure and voltage are changed, and the TiVZrNbHfCrB target 30 located on the second side of the die-casting mold away from the CrTi target is turned on under the conditions of 0.5Pa and -50V. When the workpiece holder 50 carries the die-casting mold and rotates toward the CrTi target, a CrTiN single layer is deposited, and the thickness of the CrTiN single layer is 20 nanometers; when the workpiece holder 50 carries the die-casting mold and rotates toward the TiVZrNbHfCrB target 30, a TiVZrNbHfCrBN single layer is deposited, and the thickness of the TiVZrNbHfCrBN single layer is 20 nanometers, and this is repeated, with a modulation period of 40 nanometers, so that a 4000 nanometer thick CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is alternately formed on the surface of the CrTiN transition metal ceramic layer as a hardening layer.

[0058] Step 5: close the CrTi target, and when the workpiece holder 50 carries the die-casting mold to rotate under the conditions of 4Pa and -250V, further arc ion plate the TiVZrNbHfCrB target 30 to form a 3000 nm thick TiVZrNbHfCrBN high entropy alloy nitride layer as a wear-resistant layer outside the hardening layer;

[0059] Step 6: On the basis of step 5, maintain the pressure at 4Pa and adjust the voltage to -200V. Under this condition, introduce oxygen. In the common atmosphere of nitrogen and oxygen, the opened TiVZrNbHfCrB target 30 evaporates at high temperature, and a 1000 nanometer thick TiVZrNbHfCrBON layer is deposited outside the wear-resistant layer as an anti-aluminum liquid corrosion layer.

[0060] Step 7: Based on step 6, the pressure is adjusted to 4.3 Pa, and the nitrogen is turned off under the condition of -200 V. In the oxygen atmosphere, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature to deposit a 1000 nm thick TiVZrNbHfCrBO oxide layer outside the anti-aluminum liquid corrosion layer as a low surface energy aluminum liquid repellent layer.

[0061] Step 8: After the preparation is completed, the die-casting mold is naturally cooled to obtain a low surface energy, corrosion-resistant, high-entropy composite coating on the surface of the die-casting mold with good bonding strength, wear resistance, temperature resistance, and resistance to aluminum liquid corrosion to cope with the effect of high-temperature aluminum liquid.

[0062] like Figure 2As shown, the low surface energy corrosion-resistant high entropy composite coating of the above-mentioned die-casting mold includes a gradient structure composed of a bonding layer 2, a transition layer 3, a hardening layer 4, a wear-resistant layer 5, an anti-aluminum liquid corrosion layer 6, and a low surface energy aluminum-phobic liquid layer 7 from the surface of the die-casting mold 1 from the inside to the outside; the bonding layer 2 is a pure CrTi layer; the transition layer 3 is a CrTiN transition metal ceramic layer; the hardening layer 4 is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer 5 is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-aluminum liquid corrosion layer 6 is a TiVZrNbHfCrBON layer; the low surface energy aluminum-phobic liquid layer 7 is a TiVZrNbHfCrBO oxide layer.

[0063] The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers. The number of layers of the hardening layer 4 in the figure is only an example to indicate that it is a multi-layer alternating superposition structure, and does not reflect the actual number.

[0064] The TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals in the columnar crystal structure is 30-100 nanometers.

[0065] The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline size is 30 to 50 nanometers, and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer. The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0066] The general high entropy coating is mainly composed of nitrides, which mainly improve the wear resistance life of the mold. However, the coating of this embodiment requires not only high wear resistance, but also good resistance to aluminum liquid corrosion.

[0067] Compared with conventional die-casting mold coatings, this embodiment makes full use of nano multi-layer composite and gradient composite coating technology to form a gradual change in structure and composition. The coating and the substrate are metallurgically bonded to improve the compatibility of the coating and the substrate, and have good adhesion. Compared with conventional arc ion plating technology, the multi-layer structure technology is used to inhibit the growth of columnar crystals and improve the density of the coating, which not only improves the corrosion resistance of the coating, but also greatly improves the wear resistance. Fourth, the present invention combines TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings to construct a gradient high entropy composite coating, and uses the advantages of the performance of the three to construct a coating with excellent comprehensive performance of wear resistance, corrosion resistance and low surface energy.

[0068] The TiVZrNbHfCrBON high entropy composite coating die-casting mold prepared by the present invention has good bonding force and wear resistance, temperature resistance and aluminum liquid corrosion resistance, ensures the long-term stable operation of the die-casting mold, greatly improves the processing performance of the die-casting mold, stabilizes the processing quality, improves the processing efficiency, and reduces the production cost of the manufacturer.

[0069] In this embodiment, the change of coating composition is mainly achieved by introducing gas, without using a variety of complex target materials, which reduces the cost of target materials, makes the preparation of coating more economical, and makes the process more convenient.

[0070] Embodiment 3

[0071] The steps of preparing a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold include:

[0072] Step 1: Open Figure 1 In the equipment shown, the heater 20 is turned on, the temperature of the vacuum chamber is adjusted to 350°C, argon gas is introduced, and the etching source 10 is turned on to perform arc discharge plasma etching on the die casting mold. After the ion cleaning is completed, the surface of the mold substrate is in a relatively clean state. Ion etching cleaning is a prerequisite for adhesion. However, the subsequent preparation process is also a necessary supplement to obtain high adhesion. Generally, the ion bombardment method is used to further improve the adhesion.

[0073] Step 2: After the plasma etching is completed, the CrTi target 60 located on the first side of the die-casting mold is opened, and the die-casting mold is rotated under the conditions of 0.2Pa and -80V. The CrTi on the CrTi target 60 is evaporated at high temperature by an arc ion plating method and moved to the surface of the die-casting mold at high speed under the action of high bias voltage. A negative high voltage of 1000V is applied to the surface of the die-casting mold. The high voltage has an accelerating effect on the ionized die-casting mold ions. The accelerated die-casting mold ions will collide with the die-casting mold surface at high speed. The collision process will generate high temperature, and the CrTi ions will form a metallurgical bond with the die-casting mold substrate, thereby depositing a 30-nanometer-thick pure CrTi layer as a bonding layer.

[0074] Step 3: Based on step 2, change the pressure and voltage, and introduce nitrogen at 0.5Pa, -100V. Nitrogen reacts with CrTi to generate a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer. The thickness of the deposited CrTiN transition metal ceramic layer is 500 nanometers.

[0075] Step 4: Based on step 3, the pressure and voltage are changed, and the TiVZrNbHfCrB target 30 located on the second side of the die-casting mold away from the CrTi target is turned on under the conditions of 2.3 Pa and -100 V. When the workpiece holder 50 carries the die-casting mold and rotates toward the CrTi target, a CrTiN single layer is deposited, and the thickness of the CrTiN single layer is 10 nanometers; when the workpiece holder 50 carries the die-casting mold and rotates toward the TiVZrNbHfCrB target 30, a TiVZrNbHfCrBN single layer is deposited, and the thickness of the TiVZrNbHfCrBN single layer is 10 nanometers, and this is repeated, with a modulation period of 20 nanometers, so that a 2000 nanometer thick CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is alternately formed on the surface of the CrTiN transition metal ceramic layer as a hardening layer.

[0076] Step 5: close the CrTi target, and when the workpiece holder 50 carries the die-casting mold to rotate under the conditions of 3Pa and -100V, further arc ion plate the TiVZrNbHfCrB target 30 to form a 2000 nm thick TiVZrNbHfCrBN high entropy alloy nitride layer outside the hardening layer as a wear-resistant layer;

[0077] Step 6: On the basis of step 5, the pressure and voltage are maintained, and oxygen is introduced under the conditions of 3Pa, -100V. In the common atmosphere of nitrogen and oxygen, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature, and a 500-nanometer-thick TiVZrNbHfCrBON layer is deposited outside the wear-resistant layer as an anti-aluminum liquid corrosion layer.

[0078] Step 7: Based on step 6, the pressure is adjusted to 4.3 Pa, and the nitrogen is turned off under the condition of -100 V. In the oxygen atmosphere, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature to deposit a 1000 nm thick TiVZrNbHfCrBO oxide layer outside the anti-aluminum liquid corrosion layer as a low surface energy aluminum liquid repellent layer.

[0079] Step 8: After the preparation is completed, the die-casting mold is naturally cooled to obtain a low surface energy, corrosion-resistant, high-entropy composite coating on the surface of the die-casting mold with good bonding strength, wear resistance, temperature resistance, and resistance to aluminum liquid corrosion to cope with the effect of high-temperature aluminum liquid.

[0080] like Figure 2As shown, the low surface energy corrosion-resistant high entropy composite coating of the above-mentioned die-casting mold includes a gradient structure composed of a bonding layer 2, a transition layer 3, a hardening layer 4, a wear-resistant layer 5, an anti-aluminum liquid corrosion layer 6, and a low surface energy aluminum-phobic liquid layer 7 from the surface of the die-casting mold 1 from the inside to the outside; the bonding layer 2 is a pure CrTi layer; the transition layer 3 is a CrTiN transition metal ceramic layer; the hardening layer 4 is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer 5 is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-aluminum liquid corrosion layer 6 is a TiVZrNbHfCrBON layer; the low surface energy aluminum-phobic liquid layer 7 is a TiVZrNbHfCrBO oxide layer.

[0081] The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers. The number of layers of the hardening layer 4 in the figure is only an example to indicate that it is a multi-layer alternating superposition structure, and does not reflect the actual number.

[0082] The TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals in the columnar crystal structure is 30-100 nanometers.

[0083] The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline size is 30-50 nanometers, and the thickness of the amorphous oxide layer is 0.2-1 nanometer. The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0084] The general high entropy coating is mainly composed of nitrides, which mainly improve the wear resistance life of the mold. However, the coating of this embodiment requires not only high wear resistance, but also good resistance to aluminum liquid corrosion.

[0085] Compared with conventional die-casting mold coatings, this embodiment makes full use of nano multi-layer composite and gradient composite coating technology to form a gradual change in structure and composition. The coating and the substrate are metallurgically bonded to improve the compatibility of the coating and the substrate, and have good adhesion. Compared with conventional arc ion plating technology, the multi-layer structure technology is used to inhibit the growth of columnar crystals and improve the density of the coating, which not only improves the corrosion resistance of the coating, but also greatly improves the wear resistance. Fourth, the present invention combines TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings to construct a gradient high entropy composite coating, and uses the advantages of the performance of the three to construct a coating with excellent comprehensive performance of wear resistance, corrosion resistance and low surface energy.

[0086] The TiVZrNbHfCrBON high entropy composite coating die-casting mold prepared by the present invention has good bonding force and wear resistance, temperature resistance and aluminum liquid corrosion resistance, ensures the long-term stable operation of the die-casting mold, greatly improves the processing performance of the die-casting mold, stabilizes the processing quality, improves the processing efficiency, and reduces the production cost of the manufacturer.

[0087] In this embodiment, the change of coating composition is mainly achieved by introducing gas, without using a variety of complex target materials, which reduces the cost of target materials, makes the preparation of coating more economical, and makes the process more convenient.

[0088] Embodiment 4

[0089] The steps of preparing a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold include:

[0090] Step 1: Open Figure 1 In the equipment shown, the heater 20 is turned on, the temperature of the vacuum chamber is adjusted to 250°C, argon gas is introduced, the etching source 10 is turned on, and the die-casting mold is subjected to arc discharge plasma etching. After the ion cleaning is completed, the surface of the mold substrate is in a relatively clean state. Ion etching cleaning is a prerequisite for adhesion. However, the subsequent preparation process is also a necessary supplement to obtain high adhesion. Generally, the ion bombardment method is used to further improve the adhesion.

[0091] Step 2: After the plasma etching is completed, the CrTi target 60 located on the first side of the die-casting mold is opened, and the die-casting mold is rotated under the conditions of 0.15Pa and -50V. The CrTi on the CrTi target 60 is evaporated at high temperature by an arc ion plating method and moved to the surface of the die-casting mold at high speed under the action of high bias voltage. A negative high voltage of 1000V is applied to the surface of the die-casting mold. The high voltage has an accelerating effect on the ionized die-casting mold ions. The accelerated die-casting mold ions will collide with the die-casting mold surface at high speed. The collision process will generate high temperature, and the CrTi ions will form a metallurgical bond with the die-casting mold substrate, thereby depositing a 15-nanometer thick pure CrTi layer as a bonding layer.

[0092] Step 3: Based on step 2, change the pressure and voltage. Under the conditions of 1Pa and -100V, introduce nitrogen. Nitrogen reacts with CrTi to generate a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer. The thickness of the deposited CrTiN transition metal ceramic layer is 800 nanometers.

[0093] Step 4: Based on step 3, the pressure and voltage are changed, and the TiVZrNbHfCrB target 30 located on the second side of the die-casting mold away from the CrTi target is turned on under the conditions of 2Pa and -150V. When the workpiece holder 50 carries the die-casting mold and rotates toward the CrTi target, a CrTiN single layer is deposited, and the thickness of the CrTiN single layer is 8 nanometers; when the workpiece holder 50 carries the die-casting mold and rotates toward the TiVZrNbHfCrB target 30, a TiVZrNbHfCrBN single layer is deposited, and the thickness of the TiVZrNbHfCrBN single layer is 7 nanometers, and this is repeated, with a modulation period of 15 nanometers, so that a 1500 nanometer thick CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is alternately formed on the surface of the CrTiN transition metal ceramic layer as a hardening layer.

[0094] Step 5: The CrTi target is closed, and under the condition of 3Pa and -250V, when the workpiece holder 50 carries the die-casting mold to rotate, the TiVZrNbHfCrB target 30 is further arc ion plated to form a 2500 nm thick TiVZrNbHfCrBN high entropy alloy nitride layer outside the hardening layer as a wear-resistant layer;

[0095] Step 6: Based on step 5, oxygen is introduced under the conditions of 2.5Pa and -150V. In the common atmosphere of nitrogen and oxygen, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature, and a 800-nanometer-thick TiVZrNbHfCrBON layer is deposited outside the wear-resistant layer as an anti-aluminum liquid corrosion layer.

[0096] Step 7: Based on step 6, the pressure and voltage are adjusted. Under the conditions of 3Pa and -100V, the nitrogen is turned off. In an oxygen atmosphere, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature to deposit a 1000 nanometer thick TiVZrNbHfCrBO oxide layer outside the anti-aluminum liquid corrosion layer as a low surface energy aluminum liquid repellent layer.

[0097] Step 8: After the preparation is completed, the die-casting mold is naturally cooled to obtain a low surface energy, corrosion-resistant, high-entropy composite coating on the surface of the die-casting mold with good bonding strength, wear resistance, temperature resistance, and resistance to aluminum liquid corrosion to cope with the effect of high-temperature aluminum liquid.

[0098] like Figure 2As shown, the low surface energy corrosion-resistant high entropy composite coating of the above-mentioned die-casting mold includes a gradient structure composed of a bonding layer 2, a transition layer 3, a hardening layer 4, a wear-resistant layer 5, an anti-aluminum liquid corrosion layer 6, and a low surface energy aluminum-phobic liquid layer 7 from the surface of the die-casting mold 1 from the inside to the outside; the bonding layer 2 is a pure CrTi layer; the transition layer 3 is a CrTiN transition metal ceramic layer; the hardening layer 4 is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer 5 is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-aluminum liquid corrosion layer 6 is a TiVZrNbHfCrBON layer; the low surface energy aluminum-phobic liquid layer 7 is a TiVZrNbHfCrBO oxide layer.

[0099] The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers. The number of layers of the hardening layer 4 in the figure is only an example to indicate that it is a multi-layer alternating superposition structure, and does not reflect the actual number.

[0100] The TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals of the columnar crystal structure is 30 to 100 nanometers.

[0101] The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline size is 30 to 50 nanometers, and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer. The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0102] The general high entropy coating is mainly composed of nitrides, which mainly improve the wear resistance life of the mold. However, the coating of this embodiment requires not only high wear resistance, but also good resistance to aluminum liquid corrosion.

[0103] Compared with conventional die-casting mold coatings, this embodiment makes full use of nano multi-layer composite and gradient composite coating technology to form a gradual change in structure and composition. The coating and the substrate are metallurgically bonded to improve the compatibility of the coating and the substrate, and have good adhesion. Compared with conventional arc ion plating technology, the multi-layer structure technology is used to inhibit the growth of columnar crystals and improve the density of the coating, which not only improves the corrosion resistance of the coating, but also greatly improves the wear resistance. Fourth, the present invention combines TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings to construct a gradient high entropy composite coating, and uses the advantages of the performance of the three to construct a coating with excellent comprehensive performance of wear resistance, corrosion resistance and low surface energy.

[0104] The TiVZrNbHfCrBON high entropy composite coating die-casting mold prepared by the present invention has good bonding force and wear resistance, temperature resistance and aluminum liquid corrosion resistance, ensures the long-term stable operation of the die-casting mold, greatly improves the processing performance of the die-casting mold, stabilizes the processing quality, improves the processing efficiency, and reduces the production cost of the manufacturer.

[0105] In this embodiment, the change of coating composition is mainly achieved by introducing gas, without using a variety of complex target materials, which reduces the cost of target materials, makes the preparation of coating more economical, and makes the process more convenient.

[0106] Embodiment 5

[0107] The steps of preparing a low surface energy, corrosion-resistant, high entropy composite coating of a die-casting mold on the surface of the die-casting mold include:

[0108] Step 1: Open Figure 1 In the equipment shown, the heater 20 is turned on, the temperature of the vacuum chamber is adjusted to 400°C, argon gas is introduced, and the etching source 10 is turned on to perform arc discharge plasma etching on the die casting mold. After the ion cleaning is completed, the surface of the mold substrate is in a relatively clean state. Ion etching cleaning is a prerequisite for adhesion. However, the subsequent preparation process is also a necessary supplement to obtain high adhesion. Generally, the ion bombardment method is used to further improve the adhesion.

[0109] Step 2: After the plasma etching is completed, the CrTi target 60 located on the first side of the die-casting mold is opened. Under the conditions of 0.2Pa and -50V, the die-casting mold is rotated, and the CrTi on the CrTi target 60 is evaporated at high temperature by an arc ion plating method and moved to the surface of the die-casting mold at high speed under the action of high bias voltage. A negative high voltage of 900V is applied to the surface of the die-casting mold. The high voltage has an accelerating effect on the ionized die-casting mold ions. The accelerated die-casting mold ions will collide with the die-casting mold surface at high speed. The collision process will generate high temperature, and the CrTi ions will form a metallurgical bond with the die-casting mold substrate, thereby depositing a 30-nanometer-thick pure CrTi layer as a bonding layer.

[0110] Step 3: Based on step 2, change the pressure and voltage, and introduce nitrogen at 0.1Pa and -250V. Nitrogen reacts with CrTi to generate a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer. The thickness of the deposited CrTiN transition metal ceramic layer is 1000 nanometers.

[0111] Step 4: Based on step 3, the pressure and voltage are changed, and the TiVZrNbHfCrB target 30 located on the second side of the die-casting mold away from the CrTi target is turned on under the conditions of 0.5Pa and -50V. When the workpiece holder 50 carries the die-casting mold and rotates toward the CrTi target, a CrTiN single layer is deposited, and the thickness of the CrTiN single layer is 8 nanometers; when the workpiece holder 50 carries the die-casting mold and rotates toward the TiVZrNbHfCrB target 30, a TiVZrNbHfCrBN single layer is deposited, and the thickness of the TiVZrNbHfCrBN single layer is 4 nanometers. This is repeated, and the modulation period is 12 nanometers, so that a 1200 nanometer thick CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is alternately formed on the surface of the CrTiN transition metal ceramic layer as a hardening layer.

[0112] Step 5: close the CrTi target, and when the workpiece holder 50 carries the die-casting mold to rotate under the conditions of 4Pa and -250V, further arc ion plate the TiVZrNbHfCrB target 30 to form a 2000 nm thick TiVZrNbHfCrBN high entropy alloy nitride layer as a wear-resistant layer outside the hardening layer;

[0113] Step 6: Based on step 5, oxygen is introduced under the conditions of 2Pa, -50V, and the opened TiVZrNbHfCrB target 30 is evaporated at high temperature in a nitrogen and oxygen atmosphere, and a 900 nanometer thick TiVZrNbHfCrBON layer is deposited outside the wear-resistant layer as an anti-aluminum liquid corrosion layer.

[0114] Step 7: Based on step 6, the pressure and voltage are adjusted. Under the conditions of 2Pa and -100V, the nitrogen is turned off. In an oxygen atmosphere, the opened TiVZrNbHfCrB target 30 is evaporated at high temperature to deposit a 750 nm thick TiVZrNbHfCrBO oxide layer outside the anti-aluminum liquid corrosion layer as a low surface energy aluminum liquid repellent layer.

[0115] Step 8: After the preparation is completed, the die-casting mold is naturally cooled to obtain a low surface energy, corrosion-resistant, high-entropy composite coating on the surface of the die-casting mold with good bonding strength, wear resistance, temperature resistance, and resistance to aluminum liquid corrosion to cope with the effect of high-temperature aluminum liquid.

[0116] like Figure 2As shown, the low surface energy corrosion-resistant high entropy composite coating of the above-mentioned die-casting mold includes a gradient structure composed of a bonding layer 2, a transition layer 3, a hardening layer 4, a wear-resistant layer 5, an anti-aluminum liquid corrosion layer 6, and a low surface energy aluminum-phobic liquid layer 7 from the surface of the die-casting mold 1 from the inside to the outside; the bonding layer 2 is a pure CrTi layer; the transition layer 3 is a CrTiN transition metal ceramic layer; the hardening layer 4 is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer 5 is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-aluminum liquid corrosion layer 6 is a TiVZrNbHfCrBON layer; the low surface energy aluminum-phobic liquid layer 7 is a TiVZrNbHfCrBO oxide layer.

[0117] The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers. The number of layers of the hardening layer 4 in the figure is only an example to indicate that it is a multi-layer alternating superposition structure, and does not reflect the actual number.

[0118] The TiVZrNbHfCrBN high entropy alloy nitride layer is a columnar crystal structure, and the diameter of the columnar crystals of the columnar crystal structure is 30 to 100 nanometers.

[0119] The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure of a high entropy nitride wrapped by an amorphous oxide layer, wherein the nanocrystalline size is 30 to 50 nanometers, and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer. The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

[0120] The general high entropy coating is mainly composed of nitrides, which mainly improve the wear resistance life of the mold. However, the coating of this embodiment requires not only high wear resistance, but also good resistance to aluminum liquid corrosion.

[0121] Compared with conventional die-casting mold coatings, this embodiment makes full use of nano multi-layer composite and gradient composite coating technology to form a gradual change in structure and composition. The coating and the substrate are metallurgically bonded to improve the compatibility of the coating and the substrate, and have good adhesion. Compared with conventional arc ion plating technology, the multi-layer structure technology is used to inhibit the growth of columnar crystals and improve the density of the coating, which not only improves the corrosion resistance of the coating, but also greatly improves the wear resistance. Fourth, the present invention combines TiVZrNbHfCrBN, TiVZrNbHfCrBON and TiVZrNbHfCrBO coatings to construct a gradient high entropy composite coating, and uses the advantages of the performance of the three to construct a coating with excellent comprehensive performance of wear resistance, corrosion resistance and low surface energy.

[0122] The TiVZrNbHfCrBON high entropy composite coating die-casting mold prepared by the present invention has good bonding force and wear resistance, temperature resistance and aluminum liquid corrosion resistance, ensures the long-term stable operation of the die-casting mold, greatly improves the processing performance of the die-casting mold, stabilizes the processing quality, improves the processing efficiency, and reduces the production cost of the manufacturer.

[0123] In this embodiment, the change of coating composition is mainly achieved by introducing gas, without using a variety of complex target materials, which reduces the cost of target materials, makes the preparation of coating more economical, and makes the process more convenient.

[0124] The above is a detailed introduction to a low surface energy, corrosion-resistant, high entropy composite coating for a die-casting mold and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the present invention and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A low surface energy, corrosion resistant, high entropy composite coating for a die casting mold, characterized in that The invention comprises a gradient structure consisting of a bonding layer, a transition layer, a hardening layer, a wear-resistant layer, an anti-liquid aluminum corrosion layer, and a low surface energy aluminophobic liquid aluminum layer; the bonding layer is a pure CrTi layer; the transition layer is a CrTiN transition metal ceramic layer; the hardening layer is a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film; the wear-resistant layer is a TiVZrNbHfCrBN high entropy alloy nitride layer; the anti-liquid aluminum corrosion layer is a TiVZrNbHfCrBON layer; the low surface energy aluminophobic liquid aluminum layer is a TiVZrNbHfCrBO oxide layer; The CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film is formed by alternating CrTiN single layers and TiVZrNbHfCrBN single layers; the TiVZrNbHfCrBN high entropy alloy nitride layer has a columnar crystal structure.

2. The low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 1, characterized in that The thickness of the CrTiN single layer is 8 to 20 nanometers, the thickness of the TiVZrNbHfCrBN single layer is 4 to 20 nanometers, and the coating modulation period is 12 to 40 nanometers.

3. The low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 1, characterized in that The diameter of the columnar crystals in the columnar crystal structure is 30 to 100 nanometers.

4. The low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 1, characterized in that The TiVZrNbHfCrBON layer is a nanocrystalline amorphous structure in which an amorphous oxide layer encapsulates a high entropy nitride, wherein the nanocrystalline size is 30 to 50 nanometers and the thickness of the amorphous oxide layer is 0.2 to 1 nanometer.

5. The low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 1, characterized in that The crystal structure of the TiVZrNbHfCrBO oxide layer is an amorphous structure.

6. The low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 1, characterized in that The thickness of the bonding layer is 5 to 30 nanometers, the thickness of the transition layer is 200 to 1000 nanometers, the thickness of the hardening layer is 1200 to 4000 nanometers, the thickness of the wear-resistant layer is 2000 to 3000 nanometers, the thickness of the anti-aluminum liquid corrosion layer is 500 to 1000 nanometers, and the thickness of the low surface energy aluminum-phobic liquid layer is 500 to 1000 nanometers.

7. A method for preparing a low surface energy, corrosion resistant, high entropy composite coating for a die casting mold, characterized in that The coating is prepared by arc ion plating, which at least includes the following steps: Step 1: In an argon environment, the die-casting mold is cleaned by plasma etching; Step 2: The CrTi target located on the first side of the die-casting mold is turned on, and the die-casting mold is rotated to evaporate the CrTi at high temperature and move it to the surface of the die-casting mold at high speed under the action of high bias voltage, and the CrTi ions are metallurgically combined with the die-casting mold matrix, and a pure CrTi layer is deposited as a bonding layer; Step 3: Based on step 2, nitrogen is introduced, and the nitrogen reacts with CrTi to form a CrTiN transition metal ceramic layer on the surface of the bonding layer as a transition layer; Step 4: On the basis of step 3, the TiVZrNbHfCrB target located on the second side of the die-casting mold away from the CrTi target is opened, and a CrTiN single layer is deposited when the die-casting mold is rotated toward the CrTi target, and a TiVZrNbHfCrBN single layer is deposited when the die-casting mold is rotated toward the TiVZrNbHfCrB target, and this process is repeated to alternately form a CrTiN / TiVZrNbHfCrBN high entropy alloy nitride multilayer film as a hardening layer on the surface of the CrTiN transition metal ceramic layer; Step 5: The CrTi target is closed, and the die-casting mold is rotated to form a TiVZrNbHfCrBN high entropy alloy nitride layer outside the hardening layer as a wear-resistant layer; Step 6: Based on step 5, oxygen is then introduced, and in a nitrogen and oxygen atmosphere, the opened TiVZrNbHfCrB target is evaporated at high temperature to deposit a TiVZrNbHfCrBON layer outside the wear-resistant layer as an anti-aluminum liquid corrosion layer; Step 7: Based on step 6, the nitrogen is turned off, and in an oxygen atmosphere, the opened TiVZrNbHfCrB target is evaporated at high temperature and deposited outside the aluminum liquid corrosion resistance layer to form a TiVZrNbHfCrBO oxide layer as a low surface energy aluminum liquid repellent layer.

8. The method for preparing a low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 7, characterized in that Step 1 is carried out at 250-550°C.

9. The method for preparing a low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 7, characterized in that Step 2 is carried out under the conditions of 0.1~0.5Pa, -50V~-100V, step 3 is carried out under the conditions of 0.1~2Pa, -100V~-250V; step 4 is carried out under the conditions of 0.5~2.3Pa, -50~-250V; step 5 is carried out under the conditions of 2~4Pa, -50~-250V; step 6 is carried out under the conditions of 2~4Pa, -50~-200V; step 7 is carried out under the conditions of 2~4.3Pa, -50~-200V.

10. The method for preparing a low surface energy, corrosion resistant, high entropy composite coating for a die casting mold according to claim 7, characterized in that After step 7, cool naturally.

Citation Information

Patent Citations

  • HfZrWMoVNbN / CrSiN high-entropy alloy nano composite coating die-casting aluminum die and preparation method thereof

    CN111014616A

  • High-temperature-resistant nano multilayer self-lubricating coating for die-casting pulling core and preparation method

    CN112501571A

  • Superhard strong toughness and high-entropy alloy nitride nano-composite coating carbide blade and preparation method thereof

    CN108642449A

  • Pressure casting aluminum mold with nanocrystalline composite coating and preparing method

    CN110373632A